A Need Analysis in Creative Writing Course for The Students of English Study Program UIN Satu Tulungagung - Ima Herminingsih, Dwi; Isro’iyah, Latifatul; Elshania Budiarti, Roro; Sholihah, An’nisa (International Journal of Social Science, Education, Communication and Economics, 2024)
Need analysis is a process used to identify and evaluate stakeholders' requirements, desires, and expectations, which in this context are students of the English Education Department. It helps the lecturer or teacher understand students' target needs and how to meet those needs effectively. This research aims to know, the first, what kind of difficulties faced by Students of the English Education Department in the Creative Writing Course, the second the basic competence and the third is the material that is seen as necessary and not necessary to be taught by the English Education Department Students in Comprehending Creative Writing Course. The needs analysis was completed by distributing questionnaire items to 40 students in the 5th semester of the English Education Department as respondents to answer questions which areas related with the previously mentioned aims of study. The result of analysis indicates that most students regarded writing novels as the most challenging competence of the creative writing course than writing poems and short stories. Then, the most urgent English material that should be taught in the writing course is understanding grammar and vocabulary.